2014
DOI: 10.1074/jbc.m114.551804
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular UDP-Glucose Activates P2Y14 Receptor and Induces Signal Transducer and Activator of Transcription 3 (STAT3) Tyr705 Phosphorylation and Binding to Hyaluronan Synthase 2 (HAS2) Promoter, Stimulating Hyaluronan Synthesis of Keratinocytes

Abstract: Background:The secretion and possible functions of extracellular UDP-sugars in epidermal keratinocytes are not known. Results: UDP-glucose activates P2Y 14 receptor and JAK2, increases STAT3 Tyr 705 phosphorylation, and enhances transcription of hyaluronan synthase 2 (HAS2). Conclusion: UDP-glucose release signals for enhanced HAS2 expression by keratinocytes. Significance: Stimulation of hyaluronan synthesis is an inherent part of epidermal keratinocyte activation and injury response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 61 publications
2
47
0
Order By: Relevance
“…Selective antagonist for P2Y 14 receptor has not yet been identified. PTX, known as an inhibitor of G i -coupled receptor (Jacobson et al, 2009;Jokela et al, 2014), was used to assess the activation of P2Y 14 receptor induced by OGD in this experiment.…”
Section: Groups and Drug Administrationmentioning
confidence: 99%
“…Selective antagonist for P2Y 14 receptor has not yet been identified. PTX, known as an inhibitor of G i -coupled receptor (Jacobson et al, 2009;Jokela et al, 2014), was used to assess the activation of P2Y 14 receptor induced by OGD in this experiment.…”
Section: Groups and Drug Administrationmentioning
confidence: 99%
“…So far eight subtypes of P2Y subfamily have been (Pelegrin et al, 2008;Qu et al, 2011). Like P2X, P2Y receptors also differ in their agonist binding profiles, with one group specific to adenine nucleotides (P2Y 1 , P2Y 12 , P2Y 13 ), another group (P2Y 2 and rodent P2Y 4 ) activated by both adenine and uridine nucleotides, a third group specific to uridine nucleotides (human P2Y 4 and P2Y 6 ) and P2Y 14 activated by UDP-glucose (Jokela et al, 2014). All known subtypes of P2Y receptors are expressed in the CNS with variable distribution among different cell types (i.e.…”
Section: The Role Of P2y Receptors In Neuroinflammationmentioning
confidence: 99%
“…A recent study showed that HA does not contribute to the growth and differentiation of human epidermal keratinocyte (Malaisse et al, 2016). Nevertheless, UDP-glucose induces HA synthesis in keratinocytes via P2Y14 receptor, STAT3 signaling and activation of hyaluronan synthase (HAS) promoter (Jokela et al, 2014). The conformation of HA in solution is readily subjected to changes upon altering the compositions of solvents, and this affects the functional properties of HA in many biological processes such as interactions with complement proteins and their associated hemolytic function (Chang and Boackle, 1985; Chang et al, 1985; Hong et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%